Differences in DNA methylation of HAMP in blood cells predicts the development of type 2 diabetes - Meriem Ouni; Fabian Eichelmann; Markus Jähnert; Christin Krause; Sophie Saussenthaler; Christiane Ott; Pascal Gottmann; Thilo Speckmann; Peter Huypens; Stefan Wolter; Oliver Mann; Martin Hrabé De Angelis; et al. (Elsevier, 2023)
Objectives: Better disease management can be achieved with earlier detection through robust, sensitive, and easily accessible biomarkers. The aim of the current study was to identify novel epigenetic biomarkers determining the risk of type 2 diabetes (T2D). Methods: Livers of 10-week-old female New Zealand Obese (NZO) mice, slightly differing in their degree of hyperglycemia and liver fat content and thereby in their diabetes susceptibility were used for expression and methylation profiling. We screened for differences in hepatic expression and DNA methylation in diabetes-prone and -resistant mice, and verified a candidate (HAMP) in human livers and blood cells. Hamp expression was manipulated in primary hepatocytes and insulin-stimulated pAKT was detected. Luciferase reporter assays were conducted in a murine liver cell line to test the impact of DNA methylation on promoter activity. Results: In livers of NZO mice, the overlap of methylome and transcriptome analyses revealed a potential transcriptional dysregulation of 12 hepatokines. The strongest effect with a 52% decreased expression in livers of diabetes-prone mice was detected for the Hamp gene, mediated by elevated DNA methylation of two CpG sites located in the promoter. Hamp encodes the iron-regulatory hormone hepcidin, which had a lower abundance in the livers of mice prone to developing diabetes. Suppression of Hamp reduces the levels of pAKT in insulin-treated hepatocytes. In liver biopsies of obese insulin-resistant women, HAMP expression was significantly downregulated along with increased DNA methylation of a homologous CpG site. In blood cells of incident T2D cases from the prospective EPIC-Potsdam cohort, higher DNA methylation of two CpG sites was related to increased risk of incident diabetes. Conclusions: We identified epigenetic changes in the HAMP gene which may be used as an early marker preceding T2D.